The Influence of the Implementation of the Village Financial System Application, Human Resource Competence and Internal Control System on the Quality of Village Government Financial Reports in Batang Tuaka District - Rosliana Rosliana; Haryadi Haryadi; Achmad Hizazi; Yudi Yudi (PT. Anagata Sembagi Education, 2026)
This study aims to analyze the influence of village governance and the implementation of the Village Financial System (Siskeudes) on the implementation of village finances in the Kempas District. The main problems underlying this study are the low capacity of village officials, the suboptimal utilization of digital systems, and the gap between regulations and implementation in village financial management. The research method used is a qualitative approach with data collection techniques through observation, interviews, and documentation, and analyzed using the stages of data reduction, data presentation, and conclusion drawing. The results show that village governance and the implementation of Siskeudes have a positive effect on the implementation of village finances, especially in increasing transparency, reporting accuracy, and administrative efficiency. However, the effectiveness of Siskeudes implementation is greatly influenced by the competence of village officials in operating the system and their level of understanding of accounting principles and information technology. The discussion emphasizes that the integration of good governance and the use of digital technology is key to realizing optimal implementation of village finances. In conclusion, improving the implementation of village finances requires a comprehensive approach through strengthening governance, optimizing the use of Siskeudes, increasing human resource capacity, and active community involvement.